Analysis of rock cavern stability - Teong, Wei Kok (2017)
Development into underground space has been made easier due to the advancement in tunnelling and excavation methods. Also, with the advancement in finite element software, analysis for rock cavern stability can be easily carried out. This allows feasibility studies to be carried out at a faster rate with higher accuracy thus leading to a more efficient analysis. This project aims to utilize Plaxis, finite element modelling software to carry out analysis on factors affecting the stability of an unsupported rock cavern during excavation. The results of this analysis include the Factor of Safety (FS), crown and sidewall displacement. The results indicated that the stability of an unsupported rock cavern during excavation are generally affected by the volume of excavated rocks, the lesser the volume of excavated rocks, the more stable the cavern will be during excavation. However, for weaker rock masses, the dimension for the rock cavern is more significant in the stability for the rock cavern whereas the volume of the excavated rocks will govern the stability for the stronger rock masses.